Nucleoporin POM121 signals TFEB-mediated autophagy via activation of SIGMAR1/sigma-1 receptor chaperone by pridopidine. Issue 1 (2nd January 2023) - Wang, Shao-Ming; Wu, Hsiang-En; Yasui, Yuko; Geva, Michal; Hayden, Michael; Maurice, Tangui; Cozzolino, Mauro; Su, Tsung-Ping
ABSTRACT: Macroautophagy/autophagy is an essential process for cellular survival and is implicated in many diseases. A critical step in autophagy is the transport of the transcription factor TFEB from the cytosol into the nucleus, through the nuclear pore (NP) by KPNB1/importinβ1. In the C9orf72 subtype of amyotrophic lateral sclerosis-frontotemporal lobar degeneration (ALS-FTD), the hexanucleotide (G4C2)RNA expansion (HRE) disrupts the nucleocytoplasmic transport of TFEB, compromising autophagy. Here we show that a molecular chaperone, the SIGMAR1/Sigma-1 receptor (sigma non-opioid intracellular receptor 1), facilitates TFEB transport into the nucleus by chaperoning the NP protein (i.e., nucleoporin) POM121 which recruits KPNB1. In NSC34 cells, HRE reduces TFEB transport by interfering with the association between SIGMAR1 and POM121, resulting in reduced nuclear levels of TFEB, KPNB1, and the autophagy marker LC3-II. Overexpression of SIGMAR1 or POM121, or treatment with the highly selective and potent SIGMAR1 agonist pridopidine, currently in phase 2/3 clinical trials for ALS and Huntington disease, rescues all of these deficits. Our results implicate nucleoporin POM121 not merely as a structural nucleoporin, but also as a chaperone-operated signaling molecule enabling TFEB-mediated autophagy. Our data suggest the use of SIGMAR1 agonists, such as pridopidine, for therapeutic development of diseases in which autophagy is impaired. Abbreviations : ALS-FTD, amyotrophic lateral sclerosis-frontotemporal dementiaC9ALS-FTD, C9orf72 subtype of amyotrophic lateral sclerosis-frontotemporal dementiaCS, citrate synthaseER, endoplasmic reticulumGSS, glutathione synthetaseHRE, hexanucleotide repeat expansionHSPA5/BiP, heat shock protein 5LAMP1, lysosomal-associated membrane protein 1MAM, mitochondria-associated endoplasmic reticulum membraneMAP1LC3/LC3, microtubule-associated protein 1 light chain 3NP, nuclear poreNSC34, mouse motor neuron-like hybrid cell lineNUPs, nucleoporinsPOM121, nuclear pore membrane protein 121SIGMAR1/Sigma-1R, sigma non-opioid intracellular receptor 1TFEB, transcription factor EBTMEM97/Sigma-2R, transmembrane protein 97